Application of a DEM-based Distributed Rainfall-Runoff Model Considering Karst Landform in the Xijiang River Basin - CHEN Shilei; XIONG Lihua; ZHA Xini; SHU Peng (Renmin Zhujiang)
Under the influence of karst landform, thehydrological Processin karstregions is quite different from that in non-karst regions, so the rainfall-runoff modelsapplicable for non-karst basins cannot be replicated to karst basins. Based on the hydrologicalcharacteristics and variability of karst landform, this paper improves a DEM-based distributedrainfall-runoff model (DDRM) for karst basins by considering the effects of epi-karst zone on waterstorage capacity and underground river system on runoff yield, and applies both the original andimproved DDRM in the Xijiang River Basin to simulate the daily runoff at the Wuzhou Station duringthe period of 2010 to 2016. The comparison of the simulation results of the two DDRM models showesthat the improved DDRM model remarkably enhances the simulation accuracy of the daily runoff andhas better simulation performance in both flood season and dry season for karst basin.